Conceptualization of Quality of the Future Teacher Training in the System of Professional Education in the Republic of Poland - Bilyakovska, Olha (Pedagogical Discourse, 2019)
The article deals with the problem of quality of the future teacher training in the Republic of Poland. It is stated that the education reforms of the beginning of the 1990-s gave a strong impetus for modernization of teacher training in the Republic of Poland. The implementation of the reforms led to radical changes in the state education policy as well as in the direction of the system of education to quality assurance. The Republic of Poland is seen to focus on the best EU examples by choosing the European vector of development in the sphere of professional training, notably teacher training. Based on scientific resources, quality of teacher training is studied considering the main paradigm of its realization. In particular, professional training must be realized in such a way that future teachers can get an opportunity to discover essence and meaning of their vocation. Taking this fact into consideration, a personality-oriented paradigm of teacher training is the most relevant to quality assurance. It is noted that humanistic and axiological approaches in teacher training should be aimed at the development of teacher’s personality, system of values, motives for innovative and creative activity, formation of self-awareness and self-development skills, but not only at professionally significant knowledge and skills. The main drawback in ensuring quality of teacher training is the focus on theoretical knowledge rather than methodological and practical knowledge. The key task in quality assurance of teacher training involves development of a reliable educational programme and defining effective ways of its realization. Reaching high standards of a future professional role in the process of teacher training is considered to be possible only due to the synergy of academic theory and practice that complement each other during training.